Intensive care nurses' lived experience of altruism and sacrifices during the Covid‐19 pandemic: A phenomenological study. (17th October 2022) - Slettmyr, Anna; Arman, Maria; Andermo, Susanne; Malmberg, Chris; Hällström, Åsa; Hugelius, Karin; Schandl, Anna
Abstract: Aim: The aim of this study was to understand the lived experience of altruism and sacrifices among Swedish nurses working in intensive care units (ICU) during the COVID‐19 pandemic. Design: This was a descriptive phenomenological study. Methods: The study was conducted between June 2020 and March 2021 and included 20 nurses who were directly involved in the ICU care of COVID‐19 patients in Sweden during the pandemic. The text transcripts were analysed using Malterud's Systematic Text Condensation. Findings: The analysis revealed four themes. The work situation changed from 1 day to another— the nurses were brutally confronted with a new and highly demanding situation. Adapting to the chaotic situation— despite fear, anguish and exhaustion, the nurses adapted to the new premises. They shouldered the moral responsibility and responded to the needs of the patients and the health care system since they had the competence. Being confronted with ethical and moral challenges— the nurses were overwhelmed by feelings of helplessness and inadequacy because despite how hard they worked, they were still unable to provide care with dignity and of acceptable quality. The importance of supporting each other— collegiality was fundamental to the nurses' ability to cope with the situation. Conclusions: Taken together, being exposed to a constantly changing situation, facing the anguish and misery of patients, families, and colleagues, and being confronted with a conflict between the moral obligation to provide care of high quality and the possibility to fulfil this commitment resulted in suffering among the nurses. Collegial back‐up and a supportive culture within the caring team were important for the nurses' endurance. Impact: The study contributes an understanding of nurses' lived experience of working during the COVID‐19 pandemic and highlights the importance of protecting and preparing nurses and nursing organisation for potential future crises.